Carbon-Interlayer SnO2–Sb2O3 Composite Core–Shell Structure Anodes for Sodium-Ion Batteries - Zhang, Guoju; Qu, Yuanduo; Zhao, Fanghui; Dang, Rongxin; Yang, Jie; Wang, Liying; Zhang, Yuanpeng; Duan, Lianfeng (Frontiers in Energy Research, 2021)
Although great efforts have been dedicated to improving electrochemical property of oxides anode material for sodium-ion batteries, the cycling life and rate capability of oxides anode materials are still far from its theoretical value. Herein, novel uniform SnO2@C@Sb2O3 submicrospheres with multilayer core–shell hollow structure have been synthesized as anode of sodium-ion batteries. The multilayer core–shell structure SnO2@C@Sb2O3 composite delivers a reversible capacity of 269 mAh g−1 at higher current density (1,500 mA g−1) after 100 cycles and exhibited excellent rate performance. The conductivity of the anode composite is promoted by the uniformly carbon dispersion through the whole submicrospheres. The dramatic volume change of electrode material could be mitigated by the porous core–shell structure of Sb2O3 and SnO2 during charge–discharge process. The enhanced specific capacity and rate performance are mainly ascribed to the integrity of structure and synergy effect between different metal oxides.